A Study of Diplomatic Discourse Strategies from the Perspective of the Attitude System - Zhou, Yuechen; Zuo, Jingyan; Jiang, Huimin (RIRAI Publisher, 2024)
ABSTRACT This study utilizes the “Spokesperson’ s Remarks” section on the official website of the Ministry of Foreign Affairs of the People’ s Republic of China, focusing on over 100,000 words from the regular press conferences held by the Ministry in 2023. Drawing upon Martin and White’ s (2005) appraisal theory as the analytical framework, this research conducts frequency statistics and functional discourse analysis on the categories of attitudinal resources in the selected corpus. Employing a combination of qualitative and quantitative approaches, the study aims to identify and investigate the discourse meanings conveyed through attitude resources in the news discourse of “regular press conferences,” revealing the linguistic characteristics of China’ s diplomatic discourse. Furthermore, it seeks to summarize the significance and impact of diplomatic discourse on the construction of national image. The results indicate that the corpus is most rich in judgmental attitude resources, primarily realized through vocabulary, syntax, and rhetorical expressions. This suggests that spokespersons mainly express attitudinal tendencies through factual statements and enhance national discourse power with precise language control, reflecting the objectivity of the discourse and contributing to the audience’ s trust in the information.